Measurement of vaccination coverage at age 24 and 19-35 months: a case study of multiple imputation in public health - Shaw Kate M; Barker Lawrence E; Santibanez Tammy A (BMC, 2005)
Abstract Aim Childhood immunization coverage in the United States (U.S.) is often measured at age 24 months or, in the National Immunization Survey (NIS) at age of interview, which is between 19 and 35 months. This paper compares these standards. Methods Data from the NIS is used to compare immunization coverage at time of interview, retrospectively among all children aged 24 or more months at time of interview, and obtained via multiple imputation (with 10 imputations) for all children, both nationally, by state, and by demographic groups. Results At the national level, the difference between the 19-35 month estimate and the 24 month complete-case estimate was 1.9 percentage points. For most but not all states and subgroups, the 19-35 month estimate was higher than the 24 month complete-case estimate. The difference between vaccination coverage measured at 19-35 months and 24 months ranged from -2.3 to 7.5 percentage points among states. For three states, the difference between the 19-35 month and 24 month complete-case estimate was more than 6 percentage points, in twelve states there was a 4-6 percentage point difference, and in sixteen states a 2-4 percentage point difference. Conversely, five states had higher 24 month complete-case estimates than 19-35 month estimates. Conclusion We found that the coverages at 19-35 and 24 months differ such that they would rarely be adequate surrogates for one another, particularly at a state level. Multiple imputation, which is easily implemented, increases precision of estimates of coverage at age 24 months.